The Implication of Multi-System and Fluency Bridge Method in Learning English to the Learning Result of Students in Hary English Course for Elementary Level - Siti Zulfah (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
The low level of English mastery of learners in Indonesia, which is categorized far from the target, can be seen from the inappropriate application and implementation of English learning systems and methods that are applied in most formal educational institutions that are different from English course institutions. This research is aimed to determine the implication of the multi-system and the fluency bridge method for the enhancement of English mastery of HEC students. The object of the research is 3 students of elementary level of Hary English Course branch Manggisan Indah residential area, Wonosobo. The research has been conducted for approximately 4 months, started from April to July and October to November in 2019 with a private class system. Each class has a different elementary level namely level 1 and 5 elementary accompanied by different learning materials and methods. The result of the research stated that the application of multi-system and fluency bridge method was proven effectively to improve the understanding and the English abilities of HEC elementary students in Wonosobo. This statement is proven through the observation of HEC students before joining and after taking the course, showing a drastic difference in their ability to speak English. This is also showed in their level of interest in learning English, the speed level of understanding the given materials and the results of the post-test which states they graduated from the level that just learned.